I am studying about Larange Multiplier on MIT OCW and I stumbled through an algebra step that I'm not quite sure about.

These are the pics from the lecture.

The equations - pic 1

Matrix transformation - pic 2

Please help me explain how he translates the system of equations into matrices form and then determine the solution. Plus, why is the determinant of matrix M in this case equals to C would give the solution?

What should I take in order to understand these concept more in depth? (I'm guessing linear algebra but I'm not too sure).

Thank you very much!


Well, to answer a part of your question: look at the matrix vector multiplication and actually calculate the result:

$ \begin{bmatrix} 2 & -\lambda\\ \lambda & -2 \end{bmatrix} \cdot \begin{bmatrix}x\\y\end{bmatrix} = \begin{bmatrix}2x-\lambda y\\ \lambda y -2x\end{bmatrix} = \begin{bmatrix}0\\0\end{bmatrix} $

There you find again your equations

$ 2x-\lambda y = 0 $ and $ \lambda y -2x = 0 $

You can always bring a linear system of equations into matrix form by letting the matrix $M$ be the matrix of coefficients, i.e. $M_{i,j}$ is the coefficient in the i-th equation of the j-th variable.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.